Violence, Virtue and Spiritual Liberation: A Preliminary Survey of Buddhist and Jaina Stories of Future Rebirths of Srenika Bimbisara and Kunika Ajatasatru - Wu, Juan (Religions of South Asia, 2014)
The Magadhan king Srenika Bimbisara and his son Kunika Ajatasatru are widely featured in both Buddhist and Jaina literature. Previous studies have generally focused on the parallels between Buddhist and Jaina depictions of these two figures. Rather less attention has been devoted to exploring how or why the Buddhist and Jaina stories about them differ. This article contrasts the Buddhist and Jaina accounts of their future rebirths. Whereas the Jainas spoke much of Srenika's eventual jinahood and kept silent on Kunika's future destiny, the Buddhists said little about Bimbisara's future destiny, while giving several prophecies of Ajatasatru's eventual awakening. Based on a comparative survey of the Buddhist and Jaina accounts, the article argues that the Buddhist and Jaina authors held significantly different understandings of how key religious factors such as karma, the Dharma, the power of the Buddha or Mahavira, and an individual's inherent spiritual potential play out in soteriological discourse. It also argues that the Buddhist prophecies of Ajatasatru and the Jaina prophecies of Srenika share a common idea that moral culpability has no permanent karmic effects, thus constituting no real obstacle to spiritual growth in the long run.